A study on healing of peptic ulcer disease after eradication of helicobacter pylori infection - Alam, Md Razibul; Ahmed, Ershad Uddin; Rahman, Md Zahidur; Islam, ASM Nazmul; Khan, Md Masudur Rahman; Ahmed, Dewan Saifuddin; Masud, Hasan; Raihan, ASMA (Bangladesh Medical Journal, 2014)
There is intimate connection between peptic ulcer & Helicobacter pylori infection. But some uncertainties still surround the relationship between status of H. pylori infection and extent & time required for ulcer healing. This prospective observational study was carried out in the department of Gastroenterology, BSMMU, Dhaka from January 2007 to January 2008 to determine whether the successful eradication of H. pylori leads to adequate ulcer healing. To see the pattern of endoscopic findings in patients still having H. pylori infection after standard triple therapy for H. pylori were also a objective. Eighty nine consecutive patients, aged 15-60 years and of both genders, coming to the gastroenterology outpatient department with the symptoms suggestive of peptic ulcer disease and dyspepsia were included and H. pylori status was defined as positive if both rapid urease test & histopathology were positive. As found in this study, H. pylori was associated with 90% of duodenal ulcers and 80% of gastric ulcers. H. pylori eradication rate was 69%. Healing rate of duodenal ulcer and gastric ulcer after standard triple therapy for 14 days were 80% and 78% respectively. Adequate ulcer healing was achieved in this study despite relatively low eradication rate. Follow-up for additional period is required for recurrence of ulcer in 84 patients whose peptic ulcer disease had resolved but could not attain H. pylori eradication and H. pylori eradicated patients who are still having ulcer at endoscopy DOI: http://dx.doi.org/10.3329/bmj.v43i2.21388 Bangladesh Med J. 2014 May; 43 (2): 84-89